Farmers or Squatters? Collective Land Claims on Sisal Estates, Tanzania (1980s–2000s). (1st March 2016) - Greco, Elisa
Abstract : This paper offers a historically grounded analysis of the land question by analysing the political history of collective land claims in sisal estates in Tanga region, in north‐east Tanzania. The persistence of sisal plantations amidst failed attempts at land redistribution is explored by drawing on primary research in villages in the vicinity of three privatized sisal estates. I situate collective land claims in the wider politics of African socialism (ujamaa), to then explain their gradual demise throughout the 1990s as a consequence of neoliberal policies such as privatization and liberalization. Throughout the 2000s, the subsequent allocation of contested lands to commercial sisal contract farmers has fuelled further land disputes. An account of land claims over time, coupled with a class analysis of sisal contract farming, underlines the continuing relevance of the land question in areas of historical land dispossession.